2016
DOI: 10.1080/21688370.2016.1162348
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in salivary gland tight junctions

Abstract: Tight junctions form a continuous intercellular barrier between epithelial cells that is required to separate tissue spaces and regulate selective movement of solutes across the epithelium. They are composed of strands containing integral membrane proteins (e.g., claudins, occludin and tricellulin, junctional adhesion molecules and the coxsackie adenovirus receptor). These proteins are anchored to the cytoskeleton via scaffolding proteins such as ZO-1 and ZO-2. In salivary glands, tight junctions are involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
14

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 123 publications
(173 reference statements)
0
23
0
14
Order By: Relevance
“…The morphological impairements of SMGs and PGs are relevent to their functions. TJ‐based paracellular fluid secretion largely represents the functions of salivary glands, which play a dynamic role in salivary secretion (Peppi and Ghabriel, 2004; Baker, 2016; Yano et al , 2017). The expression and organization of TJ proteins are altered during several pathological processes of xerostomia (Ewert et al , 2010; Mellas et al , 2015; Ding et al , 2017; Cong et al , 2018; Zhang et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The morphological impairements of SMGs and PGs are relevent to their functions. TJ‐based paracellular fluid secretion largely represents the functions of salivary glands, which play a dynamic role in salivary secretion (Peppi and Ghabriel, 2004; Baker, 2016; Yano et al , 2017). The expression and organization of TJ proteins are altered during several pathological processes of xerostomia (Ewert et al , 2010; Mellas et al , 2015; Ding et al , 2017; Cong et al , 2018; Zhang et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, these proteins are critical for salivary gland function as they allow unidirectional fluid secretion as well as maintain a fence between apical and basolateral compartments for secretory function and need to be better understood. [33][34][35] A limitation of this study is that we only studied the scaffold protein, ZO-1, which links transmembrane tight junction proteins to the cytoskeleton. [36][37][38][39] Therefore, future studies including the transmembrane proteins (i.e., occludin, claudins, junctional adhesion molecules, ticellulin, and Coxsackieadenovirus receptors) will be necessary to confirm that tight junction proteins are completely lost after irradiation of the glands.…”
Section: Discussionmentioning
confidence: 99%
“…336 Several authors reported previously about TJ organization and expression in salivary epithelium cell models and salivary gland tissue. 336,337,338,339 A major topic of several studies is the relationship between the expression of different claudins and the corresponding barrier functionality, especially in immortalized rat salivary gland epithelial cell lines such as SMIE, SMG-C6, Par-C10 or Par-C5 (Table 4). In more detail, SMIE cells were reported to have a limited claudin expression profile, which was in line with their low barrier function, indicated by low TEER and high dextran flux.…”
Section: Tight Junctions (Tjs)mentioning
confidence: 99%